Basic laws on the structure of the Soviet State - translated and edited by Harold J. Berman and John B. Quigley, Jr. (Harvard University Press, 1969)
Constitution of the USSR.--Constitution of the RSFSR.--Rules of the Communist Party of the Soviet Union.--General statute on USSR ministries.--Statute on elections to the Supreme Soviet.--Statute on permanent commissions of the Supreme Soviet.--Edict on rural soviets.--Statute on the city soviet.--Statute on permanent commissions of local soviets.--Statute on the Committee of Party-State Control.--Statute on procuracy supervision.--Statute on the Supreme Court.--Statute on military tribunals.--Law on court organization.--Statute on elections of people's courts.--Statute on State arbitrazh.--Temporary rules on courts of conciliation.--Statute on comrades' courts.--Statute on administrative commissions.--Statute on the State notariat.--Statute on the advocates.--Model statute on the jurisconsult.